MANAJEMEN KOMUNIKASI PELAKSANAAN OPERASI AMAN NUSA II MADAGO RAYA 2021 POLRES SIGI DALAM PERCEPATAN DAN ANTISIPASI WABAH COVID-19 - Israwaty Suriady; Fitriani Puspa Ningsih; Nurhaidar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2021)
This article is based on the spread of the Covid-19 outbreak in Indonesia, including in the Central Sulawesi Province. In response to this, the government took various steps to handle and prevent the outbreak, one of which was implemented through the establishment of the Task Force for the Acceleration of Handling the Covid-19 Outbreak at the District and District Levels. In the Sigi Regency area, this task force works under the auspices of the Safe Operations Task Force Nusa II Madago Raya. Involving elements of the Police, TNI, and other related elements, this operation program has carried out various activities in an effort to deal with Covid-19 in the Sigi Regency area. Using qualitative methods, this study aims to see how the communication management of the Aman Nusa Madago Raya II operation of the Sigi Police Station is. The results of the study found four important stages in communication management which were described quite well in the implementation of the program.